Flame-retardant and antibacterial properties of cotton fabrics treated by epichlorohydrin-modified aramid nanofibers, ionic liquid, and Cu ion. (June 2023) - Wang, Yaxuan; Ren, Jinyong; Ou, Mingyu; Cui, Jiahui; Guan, Haocun; Lian, Richeng; Jiao, Chuanmei; Chen, Xilei
Highlights: A novel flame retardant was coated on the surface of cotton fabric via a straightforward step-by-step dip-coating method. The introduction of AEP/IL/Cu significantly solves the problem of a large number of toxic smoke gasses released from Cot/AEP/IL. Cot/AEP/IL/Cu significantly inhibited the production of toxic smoke gasses and improved the flame-retardant and antibacterial properties of the cotton fabric greatly. Abstract: To meet the demands of reducing the serious illness caused by the growth of bacteria and the severe life-threatening due to interior fabric fire, the attention to antibacterial flame-retardant cotton fabrics has reached an unprecedented height. In this work, a simple step-by-step dip-coating method was applied for the multifunctional cotton based on epichlorohydrin-modified aramid nanofibers (AEP), ionic liquid (IL), and CuSO4 . Cot/AEP/IL/Cu exhibited low flammability with a limiting oxygen index (LOI) improving from 18.5% to 28.5% and high flame retardancy (e.g., ∼43.7% and 41.7% decline in peak heat release rate (pHRR) and total heat release rate (THR)). Noticeably, the Cot/AEP/IL/Cu revealed conspicuous smoke suppression and toxic reduction property compared with Cot/AEP/IL (e.g., ∼77.0% decline in peak smoke release rate (pSPR) and 40.5% in total CO production (TCOP)). In addition, the antibacterial property of treated cotton was investigated by the agar diffusion plate method. Due to the presence of Cu ion, Cot/AEP/IL/Cu remarkably restrains the activity of E. coli and S. aureus. This work prepared a multifunctional cotton fabric integrated with flame-retardant, smoke suppression, toxicity reduction, and antibacterial in a straightforward way, which endows promising applications in many fields. Graphical abstract: Image, graphical abstract